Environmental regulation of the estuarine copepods Acartia tonsa and Eurytemora americana during coexistence period - Hoffmeyer, Monica Susana (2009)
The seasonal dynamics of Acartia tonsa and the invader Eurytemora americana were analysed in relation to the environ- mental variability occurring from April to November in the Bahia Rlanca Estuary. Twice a month, the abundance of eggs, nauplii, copepodites and adults was examined and some environmental variables were recorded. Multivariate statistics (CCA) was applied to analyse the data of variables. Acartia tonsa eggs and nauplii diminishedfrom April-May and they were almost absent between Tune and September, although a small larval peak cot~ld be detected from the end of July to October. All the stages of this species increased in number through spring. Eurytemora americana was registered as from June and only nauplii larvae were observed, with a peak increase during September. Copepodites and adults were observed as from July, increasing in number until peaking at the end ofSeptember. The number of all stages of this species decreased abruptly, the whole population disappearing from the plankton. The A. tonsa developmental stages were most positively correlated with temperature, photoperiod and other light variables whereas those of E. americana showedpositive correlations with chlorophyll-a and salinity. The gradients ofthe main environmental factors likelygive rise to a certain niche separation facilitating the coexistence of the two copepod populations within the period studied.